Cognitive Trajectories and Dementia Risk: A Comparison of Two Cognitive Reserve Measures - Gallo, Federico; Kalpouzos, Grégoria; Laukka, Erika J.; Wang, Rui; Qiu, Chengxuan; Bäckman, Lars; Marseglia, Anna; Fratiglioni, Laura; Dekhtyar, Serhiy (Frontiers in Aging Neuroscience, 2021)
Cognitive reserve (CR) is meant to account for the mismatch between brain damage and cognitive decline or dementia. Generally, CR has been operationalized using proxy variables indicating exposure to enriching activities (activity-based CR). An alternative approach defines CR as residual variance in cognition, not explained by the brain status (residual-based CR). The aim of this study is to compare activity-based and residual-based CR measures in their association with cognitive trajectories and dementia. Furthermore, we seek to examine if the two measures modify the impact of brain integrity on cognitive trajectories and if they predict dementia incidence independent of brain status. We used data on 430 older adults aged 60+ from the Swedish National Study on Aging and Care in Kungsholmen, followed for 12 years. Residual-based reserve was computed from a regression predicting episodic memory with a brain-integrity index incorporating six structural neuroimaging markers (white-matter hyperintensities volume, whole-brain gray matter volume, hippocampal volume, lateral ventricular volume, lacunes, and perivascular spaces), age, and sex. Activity-based reserve incorporated education, work complexity, social network, and leisure activities. Cognition was assessed with a composite of perceptual speed, semantic memory, letter-, and category fluency. Dementia was clinically diagnosed in accordance with DSM-IV criteria. Linear mixed models were used for cognitive change analyses. Interactions tested if reserve measures modified the association between brain-integrity and cognitive change. Cox proportional hazard models, adjusted for brain-integrity index, assessed dementia risk. Both reserve measures were associated with cognitive trajectories (β×time [top tertile, ref.: bottom tertile] = 0.013; 95% CI: -0.126, -0.004 [residual-based] and 0.011; 95% CI: -0.001, 0.024, [activity-based]). Residual-based, but not activity-based reserve mitigated the impact of brain integrity on cognitive decline (β top tertile×time×brain integrity] = -0.021; 95% CI: -0.043, 0.001) and predicted 12-year dementia incidence, after accounting for the brain-integrity status (HR [top tertile] = 0.23; 95% CI: 0.09, 0.58). The operationalization of reserve based on residual cognitive performance may represent a more direct measure of CR than an activity-based approach. Ultimately, the two models of CR serve largely different aims. Accounting for brain integrity is essential in any model of reserve.